Diversity of Snakes in Sarlahi District, Nepal - Chettri, Krishna; Thapa Chhetry, Damodar (Our Nature, 2014)
A total of 21 snake species belonging to 17 genera and 4 families were recorded. Out of 21 species, 2, 14, 4, and 1 belong to family Typhlopidae, Colubridae, Elapidae and Viperidae respectively. They have been categorized as deadly venomous, mild venomous and non-venomous. Among the recorded species 5 were deadly venomous, 4 were mild venomous and the remaining 12 were non venomous. The species of Boidae family was not encountered during the study period. DOI: http://dx.doi.org/10.3126/on.v11i2.9600 Our Nature 2013, 11(2): 201-207